Clinical outcomes of adult inpatients treated with continuous subcutaneous insulin infusion for diabetes mellitus: a systematic review. Issue 10 (31st March 2015) - Anstey, J.; Yassaee, A.; Solomon, A.
Abstract Aims To provide a systematic review of the current evidence concerning the diabetes‐related outcomes of patients provided with continuous subcutaneous insulin infusion for treating diabetes mellitus while a hospital inpatient. Methods Relevant publications were obtained from MEDLINE and EMBASE databases concerning hospital inpatients with diabetes being treated with continuous subcutaneous insulin infusion. Studies were assessed independently by two reviewers, and data on the following outcomes were extracted: inpatient mortality; clinical complications, e.g. diabetic ketoacidosis; hyperglycaemia; hypoglycaemia; length of hospital stay; mean bedside glucose level; and glucose level on discharge. Obstetric cases were examined separately to look at maternal and neonatal glycaemic outcomes. Results A total of 11 studies met the required criteria and were analysed in detail, 5 of which were predominantly obstetric. No significant complications were reported, with no incidences of death, ketoacidosis or severe hypoglycaemia. Length of hospital stay appeared to be shorter in those patients who remained on continuous subcutaneous insulin infusion, while data on mild hyperglycaemia and hypoglycaemia were inconclusive. Conclusions There are limited data available to form a significant conclusion about the safety of continuous subcutaneous insulin infusion continuation in hospital; however, its use can be justified with the presence of a specialized inpatient diabetes team for advice and support and an alternative treatment regime (e.g. subcutaneous basal bolus) should be accessible if the need were to arise.